Effectiveness of Health Education Through Video and Leaflet Media on the Level of Knowledge of Mothers about the Prevention of Dengue Fever in Toddlers - Sulistyawati Sulistyawati; Siti Aminah (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: According to WHO, 3.9 billion people in 128 countries are at risk of contracting the dengue virus. It is predicted that there are 100 million cases of dengue fever in Southeast Asia, with 500,000 cases requiring hospitalization. According to WHO, Indonesia has the greatest number of DHF cases in Southeast Asia, with 52,313 cases reported since early 2022 and 448 deaths. Objective: Understanding the impact of health education by video media and booklets on mothers' knowledge of preventing dengue hemorrhagic fever in toddlers. Methods: A quasi-experimental one-group pretest-posttest design was used. This study included up to 40 moms of toddlers whose children were treated at the Cilandak Jakarta Marine Hospital in October-November 2022. Total sampling is the sampling technique used. Results: Prior to receiving health education, the majority of respondents had sufficient knowledge (37.8) and subsequently had good knowledge (73.0). There is an effect of health education by video media and booklets on the degree of awareness of mothers on preventing dengue hemorrhagic fever in toddlers (p.value 0.000). Conclusions and Suggestions: There is evidence that health education through video media and brochures improves mothers' awareness of preventing dengue hemorrhagic fever in toddlers. To combat the spread of dengue fever, it is hoped that they would always live a clean and healthy life by doing 3M in each dwelling.